Hockey's Hidden Gods: The Untold Story of a Paralympic Miracle on Ice - Megale, S. C. (Rowman & Littlefield Publishers, 2022)
A Library Journal Best Arts & Humanities Book 2022 The extraordinary true story of the U.S. sled hockey team that overcame physical adversity and internal strife to win Paralympic gold. When former NHL star Rick Middleton accepted the position of head coach for the United States sled hockey team, he wasn’t sure what to expect. The program had never medaled—had never even come close, in fact. But where Middleton might have found despair, he instead found an incredible group of men who had battled their way back from hell to play the sport they love. In Hockey’s Hidden Gods: The Untold Story of a Paralympic Miracle on Ice, S.C. Megale uncovers the remarkable tale of a team that shocked the world by taking U.S. sled hockey from worst to first in the 2002 Paralympics. Odds of winning were dismal. The road to victory seemed unfathomable. But this cast of fifteen athletes with disabilities, athletes who had helped build a groundbreaking U.S. sled hockey program with almost no outside support, ultimately persevered on the global stage. Featuring a fascinating history of sled hockey, exclusive interviews with players and coaches, action-packed game coverage, and intimate profiles sharing the players’ personal journeys, Hockey’s Hidden Gods is the uplifting story of how once-shattered dreams can be reborn and rebuilt through tenacity, grit, and an indomitable spirit.